The partisan : a romance of the revolution - Simms, William Gilmore, 1806-1870 (Simms series., 2011)
The writings of William Gilmore Simms (1806-1870) provide a sweeping fictional portrait of the colonial and antebellum South in all of its regional diversity. Simms's account of the region is more comprehensive than that of any other author of his time; he treats the major intellectual and social issues of the South and depicts the bonds and tensions among all of its inhabitants. By the mid-1840s Simms's novels were so well known that Edgar Allan Poe could call him ""the best novelist which this country has, on the whole, produced."" The thirteenth volume in the ongoing Arkansas Edition of the.